In situ observation of the capillary infiltration of molten silicon in a SiC/SiC composite by X-ray radiography. Issue 5 (May 2022) - Carpentier, H.; Caty, O.; Le Petitcorps, Y.; Maire, E.; Marchais, A.; Eberling-Fux, N.; Couégnat, G.
Abstract: Capillary infiltration is an innovative fabrication method for metal and ceramic-matrix composites. SiC/SiC composites can be infiltrated by molten silicon to decrease residual porosity. Physical and chemical mechanisms involved during Liquid Silicon Infiltration (LSI) are complex to analyse. An in situ observation setup for capillary infiltration of molten silicon has been designed for synchrotron observations. The setup reproduces the extreme high temperature and high vacuum conditions used in the LSI process. It is also designed for X-ray observations in synchrotron beamlines and tomography stages. Sets of 2D X-ray absorption radiographs were acquired at high frequency during the LSI process. The study outlines the capillary infiltration mechanisms of molten silicon inside SiC/SiC composites. It proves that full saturation of the composite is not directly achieved after the rise of molten silicon. It is a two step mechanism. First, the infiltration occurs inside the intra granular porosity of the SiC powder matrix. Then, larger scale porosities such as cracks are filled. These phenomena have been discussed previously in the literature but never observed in situ.